Влияние параметров коронного разряда на эффективность элементов систем молниезащиты - Чернухин, А.Ю. (Електротехніка і електромеханіка, 2017)
Приведены результаты теоретических и экспериментальных исследований процессов формирования объемного заряда в области вершины стержневого молниеприемника. Рассмотрены особенности формирования стримерной короны
на стержневых молниеприемниках с различными конфигурациями вершины в электрическом поле грозового облака.
Установлены зависимости силы тока короны от напряженности электрического поля и высоты для каждого варианта стержня. Показано, что при этом временные параметры импульсов тока стримера меняются не более чем на
30%, а заряд стримера, и как следствие, сила тока короны увеличиваются по мере роста напряженности электрического поля. Предложено метод измерения скорости продвижения стримера. Метод основан на одновременном измерении напряжения и тока на разрядном промежутке. Результаты предлагается учесть при сертификации молниеприемников Наведено результати теоретичних та експериментальних досліджень процесів формування об’ємного заряду в області
вершини стрижньового блискавкоприймача. Розглянуто особливості формування стримерної корони на стрижньових
блискавкоприймачах з різними конфігураціями вершини в електричному полі грозової хмари. Встановлено залежності
сили струму корони від напруженості електричного поля та висоти для кожного варіанта стрижня. Показано, що при
цьому часові параметри імпульсів струму стримеру змінюються не більше ніж на 30%, а заряд стримеру і, як наслідок,
сила струму корони, збільшуються з ростом напруженості електричного поля. Запропоновано метод вимірювання
швидкості просування стримеру. Метод базується на одночасному вимірюванні напруги та струму у розрядному проміжку. Результати пропонується врахувати при сертифікації блискавкоприймачів Purpose. Investigation of the formation of space charge in the
region of the apex of lighting rod, under the action of the electric
field of a thunderstorm cloud, to evaluate the efficiency of elements of lighting protection systems. Methodology. We have applied the mathematical simulation of electromagnetic field distribution on the top of metal rod by different forms. As a mathematical apparatus, we use the finite element method. We considered
two forms of the rod section: round and square. The round (cylindrical) rod has a sharp apex. The square rod has a flat top. The
experimental study investigates the features of corona discharge
formation. A high-voltage test equipment is created an electric
field. Experiments carried out using a configuration consisting a
potential plate and vertical rod electrode on grounded plate. The
electric field strength varied from 1 kVm-1 to 100 kVm-1. This
range corresponds to the thunderstorm condition. Results. We
have obtained a correlation between the corona current and the
strength of the electric field for various shapes of the rod top. The
results of experimental studies confirmed the correctness of the
conclusions of theoretical estimates. We show that the time parameters of streamer current pulses vary by no more than 30%,
but a streamer charge increase to three time with increasing electric field strength. We proposed and applied a method for measuring the velocity of motion of a streamer in the discharge gap. As a
result, it is established that the streamer speed is nonlinear in
time. For a discharge gap of 1.2 m, the speed varies from 1.8·104
m/s to 1.1·106
m/s. Originality. For the first time, we have carried
out a complex of studies of corona discharge parameters from
lightning protector rod to apply for the certification procedure of
ESE terminals. Practical value. Based on the set of obtained results, it is obviously that the standard NF C 17-102:2011 will not
be introduced as a national standard of Ukraine before full introduction of scientifically justified data will be include into the requirements of the standard.